Easily accessible lithium compound catalyzed mild and facile hydroboration and cyanosilylation of aldehydes and ketones - Bisai, Milan; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2018)
Simple and readily accessible lithium compounds such as 2,6-ditertbutyl phenolate lithium (1a), 1,1' dilithioferrocene (1b) and nacnac lithium (1c) are found to be efficient single site catalysts for hydroboration of...